Cover Picture: Photoreduction Dependent p‐ and n‐Type Semiconducting Field‐Effect Transistor Properties in Undoped Reduced Graphene Oxide (ChemistrySelect 24/2017). Issue 24 (22nd August 2017) - Takehira, Hiroshi; Islam, Md. Saidul; Karim, Mohammad Razaul; Shudo, Yuta; Ohtani, Ryo; Lindoy, Leonard F.; Taniguchi, Takaaki; Osada, Minoru; Hayami, Shinya
Abstract : The cover picture shows the generation of both p‐ and n‐type semiconductivity in undoped reduced graphene oxide (rGO) through a facile photo‐reduction procedure. We propose that for the short time (one day) exposure case, a comparatively milder reduction process takes place, which results in the opening of epoxy rings leading to the creation of oxygen vacancies and defect oriented p‐type semiconductivity. On the other hand, n‐type semiconductivity arises following a longer period (two day) of photoreduction, which promotes disproportionation at the carboxylic sites accompanied by loss of carbon and oxygen content and an increased N/O ratio. More information can be found in the communication by Takihera et al. (DOI:10.1002/slct.201701509 ). (Design: Hiroshi Takehira)